(untitled) (Zien Journal of Social Sciences and Humanities, 2023)
P.R.E.S. formula is revealed as a modern interactive approach to the educational process. It is highlighted that the use of the PRES formula by educators contributes to the fact that students learn to briefly express their opinion and quickly show knowledge of the studied topic.